2014
DOI: 10.1007/s10792-014-9979-8
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 levels and biomarkers of oxidative stress in glaucoma patients

Abstract: To investigate the levels of endothelin-1 (ET-1), homocysteine (Hcy), vitamins A, E, B12 and folic acid in plasma of patients with different types of glaucoma: primary open-angle glaucoma (POAG) and normotensive glaucoma (NTG). Patients were classified into 3 groups: group POAG comprised 48 patients, group NTG comprised 15 patients, and control group that comprised 75 healthy subjects. ET-1 levels were measured by ELISA, Vitamins A and E by HPLC, and Vitamin B12, homocysteine, and folic acid levels were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Romano et al [26] suggested that vitamin B 12 treatment represents a powerful strategy to accelerate not only re-epithelization, but also corneal re-innervation after mechanical injury. Contradictory results have also been reported for the association between serum vitamin B 12 and glaucoma [6,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Romano et al [26] suggested that vitamin B 12 treatment represents a powerful strategy to accelerate not only re-epithelization, but also corneal re-innervation after mechanical injury. Contradictory results have also been reported for the association between serum vitamin B 12 and glaucoma [6,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 76%
“…From the 181 studies, 168 were excluded. Finally, 13 studies [6,7,8,9,10,11,12,13,14,19,20,21,22] were included in this meta-analysis. The detailed characteristics of each included study are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant increase in plasma ET-1 and homocysteine levels in patients with POAG is related to vascular endothelial dysfunction. [12] Due to endothelial dysfunction, plasma ET-1 levels in glaucoma patients are five times higher than corresponding age-matched healthy controls. [13]…”
Section: Circulating Biomarkers In Glaucomamentioning
confidence: 99%